Facilitating the Development of Students’ Metacognitive Awareness in Speaking through Self-Assessment - Daisy Rizqi Putri (EDULANGUE, 2019)
The need of developing metacognitive ability-knowing students’ cognitive capacity, the difficulties they meet in learning, and strategies to resolve the difficulties – must be highlighted. In accordance with this need, this research aims to find out the extent of which the implementation of students’ reflection, as a self-assessment, can facilitate students’ metacognitive awareness in a speaking class. This two-cycle action research involved 25 freshmen majoring in Dentistry whose placement test scores ranged between 453 and 617. This study took place in a Free Conversation class in a Language Training Center of a private university in Yogyakarta, Indonesia. For data collection, a 52-items questionnaire entitled “Metacognitive Awareness Inventory” (MAI) adopted from Schraw and Dennison (1994) was distributed as the instrument to measure students’ metacognitive awareness before and after the action, and the participants were required to write reflections. Teacher’s journals and class discussion were taken to triangulate the findings. The findings showed that inthe first cycle, the students haven’t been able to describe their experiences including the difficulties they met during the learning as well as the strategies must be applied to overcome the difficulties. In the second cycle, most of the students have grown their metacognitive awareness as they were able to express their difficulties and the strategies in handling them. Briefly, the reflection written by the students has initiated the growth of students’ metacognitive awareness regardless some constraints appear. Thus, requiring students to reflect on their own learning and harness their metacognitive awareness may result in better learning.